2020
DOI: 10.2807/1560-7917.es.2020.25.7.1900450
|View full text |Cite|
|
Sign up to set email alerts
|

Acute hepatitis C infection among adults with HIV in the Netherlands between 2003 and 2016: a capture–recapture analysis for the 2013 to 2016 period

Abstract: Background: With regards to the global strategy towards eliminating viral hepatitis, reliable surveillance systems are essential to assess the national response for eliminating hepatitis C virus (HCV). Aim: We aimed to assess the completeness of the two national registries with data on acute HCV infection in people with HIV, and estimated the number of acute HCV infections among adults (aged ≥ 18 years) with HIV in the Netherlands. Methods: In this observational study, cases of HCV infection and reinfection am… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Our study included data from a large cohort involving nearly all PWH in care in the Netherlands. Furthermore, a recent capture-recapture analysis showed that between 2013 and 2016 99% of acute HCV infections of HIV-positive individuals registered in the Dutch National Registry for Notifiable Diseases were captured in the ATHENA cohort [25]. Thus, we believe that the coverage of data offered by the ATHENA cohort is sufficient to understand issues related to DAA treatment access at a wide-reaching level.…”
Section: Discussionmentioning
confidence: 91%
“…Our study included data from a large cohort involving nearly all PWH in care in the Netherlands. Furthermore, a recent capture-recapture analysis showed that between 2013 and 2016 99% of acute HCV infections of HIV-positive individuals registered in the Dutch National Registry for Notifiable Diseases were captured in the ATHENA cohort [25]. Thus, we believe that the coverage of data offered by the ATHENA cohort is sufficient to understand issues related to DAA treatment access at a wide-reaching level.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies successfully adopted the capture-recapture method for monitoring and surveillance of infectious diseases. Similarly to our approach, Boender et al linked the Dutch HIV Monitoring Foundation and the National Registry for Notifiable Diseases to assess annual HIV incidence [ 17 ]. In France, a more extensive three source capture-recapture analysis incorporated variables of heterogeneous catchability to estimate the HIV incidence rate in children [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although this method has been applied in other countries to analyse leishmaniasis incidence, such as Brazil, Argentina and Bolivia [21][22][23], it is the first time, to our knowledge, that it has been used in a country belonging to the WHO European region. Nevertheless, this type of study has been useful at the European level to estimate the incidence of other infections that cause a large burden of disease such as hepatitis C or malaria [24,25].…”
Section: Plos Onementioning
confidence: 99%